Pertumbuhan Bibit Kelapa Sawit (Elaeis guineensis Jacq.) dan Serapan NPK yang Diberi Kotoran Larva Kumbang Tanduk (Oryctes rhinoceros) dan NPK Di Pembibitan Utama - Aicha Yunas; Wardati Wardati; Erlida Ariani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Efforts to obtain the good quality of seedling wos required a proper fertilization that is by giving horn beetle lava feces (Oryctes rhinoceros). The aim of this research is to know the effect of the interaction of horn beetle lava feces (kolarhino) and NPK fertilizers and to the amount of NPK absorption and to get the best dose on the growth of palm oil seedlings (Elaeis guineensis Jacq.)in the main nursey.This research has been conducted in Experimental Station Agriculture Faculty in Riau UniversityPekanbaru.The study was conducted for three months from August to November 2016.Field experiments were conducted using a complete factorial randomized design and three replications. The first factor of giving kolarhino consists of four levels, namely: 0 g per plant, 25 g per plant, 50 g per plant, 75 g per plant.The second factor of NPK compound fertilizer (15:15:15) consists of four levels, namely; 0 g per plant, 2.5 g per plant, 5.0 g per plant, 7.5 g per plant.The result of this research showed that significantly influenced on increase height seedlings, the increase stem diameter root volume, root volume, dry weight of seedlings, N uptake , and uptake P. While NPK fertilizer has significant effect on leaf number, root volume, dry weight of plant, and P absorption. Giving kolarhino 50 and 75 gr per platn showed better results for the growth of oil palm seedlings. NPK fertilizer gave significant effect to the number of leaves root volume, dry weight of plants and phosphorus uptake. NPK fertilizer 2.5 gr per plant showed better result for the growth of oil palm seedlinhs. Giving kolarhino 50 and NPK fertilizer 2.5 gr per plant showed the best possible results for the growth of iol palm seedlings. Keywords: Nursery, palm oil, larval feces, NPK compound.